2014
DOI: 10.3389/fpsyg.2014.00274
|View full text |Cite
|
Sign up to set email alerts
|

Short-term plasticity of visuo-haptic object recognition

Abstract: Functional magnetic resonance imaging (fMRI) studies have provided ample evidence for the involvement of the lateral occipital cortex (LO), fusiform gyrus (FG), and intraparietal sulcus (IPS) in visuo-haptic object integration. Here we applied 30 min of sham (non-effective) or real offline 1 Hz repetitive transcranial magnetic stimulation (rTMS) to perturb neural processing in left LO immediately before subjects performed a visuo-haptic delayed-match-to-sample task during fMRI. In this task, subjects had to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 54 publications
1
7
1
Order By: Relevance
“…The increase in activity within the fusiform gyrus (Figure 3 , Table 1 ) is congruent with previously reported involvement of the lateral occipital cortex/fusiform gyrus in tactile object recognition in both blind and sighted subjects (Sadato et al, 2002 ; Amedi et al, 2003 ; Striem-Amit et al, 2012 ) or multisensory object perception (Kassuba et al, 2011 , 2014 ; Schlaffke et al, 2015 ). Alternatively, it could reflect the emergence of tactile Braille recognition mechanisms similar to those found in the VWFA (Price and Devlin, 2001 ; Cohen et al, 2002 ; Dehaene and Cohen, 2011 ), recently found in sighted whole-word tactile Braille readers (Siuda-Krzywicka et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…The increase in activity within the fusiform gyrus (Figure 3 , Table 1 ) is congruent with previously reported involvement of the lateral occipital cortex/fusiform gyrus in tactile object recognition in both blind and sighted subjects (Sadato et al, 2002 ; Amedi et al, 2003 ; Striem-Amit et al, 2012 ) or multisensory object perception (Kassuba et al, 2011 , 2014 ; Schlaffke et al, 2015 ). Alternatively, it could reflect the emergence of tactile Braille recognition mechanisms similar to those found in the VWFA (Price and Devlin, 2001 ; Cohen et al, 2002 ; Dehaene and Cohen, 2011 ), recently found in sighted whole-word tactile Braille readers (Siuda-Krzywicka et al, 2016 ).…”
Section: Discussionsupporting
confidence: 90%
“…This raised the intriguing hypothesis that LOC specialization might be related to the processing of sensory-independent 3D geometric shapes rendering, rather than related solely to visual object recognition (this was later corroborated by many studies, e.g. see (Kassuba et al, 2014;Kim and Zatorre, 2011;Kim and James, 2010;Reed et al, 2004;Stilla and Sathian, 2008;Tal and Amedi, 2009;Zhang et al, 2004). This hypothesis was further strengthen by results demonstrating LOC activations for tactile or auditory objects recognition in congenitally blind adults, namely people who did not experience any visual inputs during CPs (Amedi et al, 2010;Dormal et al, 2018;Peelen et al, 2014;Pietrini et al, 2004) (Fig.…”
Section: Loosening the Unisensory Constraints On The Emergence Of Anamentioning
confidence: 64%
“…It is also known that regions higher up in the sensory processing hierarchy, notably the antero-medial parts of the ventral temporal cortex (MNI y>-40), can host multisensory, abstract object representations (e.g. Fairhall and Caramazza, 2013 ; Kassuba et al, 2014 ). The left fusiform gyrus in particular is suggested to process object-specific crossmodal interactions ( Kassuba et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%